StSN2 enhances tuber formation in potato via upregulating of the ABA signaling pathway - Liu, Shifeng; Wang, Yichen; Li, Luopin; Yan, Lang; Wang, Xiyao; Wang, Qiang; Lai, Xianjun (Frontiers in Plant Science, 2025)
Potato is a globally significant food and economic crop, playing a crucial strategic role in ensuring global food security and promoting economic development. The Snakin/GASA (gibberellic acid-stimulated Arabidopsis) family, a group of plant antimicrobial peptides regulated by hormones, play key roles in plant growth and development through hormone signal transduction. Previous studies have shown that overexpression of StSN2 significantly increases the tuber numbers and the proportion of large tubers, suggesting that StSN2 is a critical regulator of tuber formation, although its precise mechanism remains unclear. In this study,researchers utilized CRISPR/Cas9 technology to regulate the expression level of StSN2 in potatoes, and delved into the function of StSN2 in potato tuber formation. The research results show that deletion of the StSN2 gene led to a delay of about 14 days in the formation of potato stolons, and a decrease in yield by 20-30%. Bioinformatics analysis of the StSN2 promoter identified multiple cis-regulatory elements, and exogenous ABA and GA treatments confirmed that StSN2 responds strongly to ABA induction. Further analysis of key gene expression and enzyme activities during tuber development demonstrated that StSN2 enhances the ABA signaling pathway by upregulating components such as StPYL1, StSnRK2.2/2.3/2.6, and StABI5, thereby promoting tuber formation. In conclusion, this study integrates genetic, molecular, and physiological approaches to elucidate the regulatory role of StSN2 in potato tuber formation. The findings enrich our understanding of the molecular mechanisms underlying tuber development and provide a theoretical foundation for improving potato yields and stability through molecular design.